PENGARUH PRIVATISASI, KOMPENSASI MANAJEMEN EKSEKUTIF, DAN UKURAN PERUSAHAAN PADA KINERJA KEUANGAN - Parimana, Komang Agung Surya; Wisadha, I Gede Suparta (E-Jurnal Akuntansi, 2015)
The company's performance is something that is produced by a company in a given period. The results of the performance should be measured and illustrate the empirical condition of the company. Stufiyed aimed determined  there is a significant relationships between privatizations, executives managemenst compensation, and firms size on financial performances. This is researches a conducted’s at the state-owned companyises listeding in Indonesia Stock Exchange. The sample used  13, and use the regresiones multiplle linear analysis. The test results showed that the privatization and executive management compensation significant and positive impact on financial performance, while the size of the company does not have a significant effect on the financial performance.
Keywords: privatization, compensation, financial performance